Geochemical fate of lead in contaminated residential soils following application of amendments for lead immobilization - Saleh, Hadeer; Braida, Washington; Zhang, Zhiming; Datta, Rupali; Sarkar, Dibyendu (Frontiers in Chemistry, 2026)
BackgroundLead (Pb) persists in urban soils, where its partitioning among geochemical fractions governs mobility, bioavailability, and human health risk. These fractions are strongly controlled by soil physicochemical properties, necessitating site-specific remediation strategies.MethodsThis study developed a site-specific Pb immobilization framework linking amendment selection to soil geochemistry and sustainability considerations. Pb-contaminated residential soils from three U.S. cities, San Antonio (alkaline), Baltimore (acidic), and Detroit (near-neutral), were treated with gypsum, biochar + lime, and alum, respectively. Changes in Pb speciation were tracked using sequential extraction over 7, 30, and 90 days.ResultsAll amendments significantly reduced exchangeable Pb (F1) and increased less mobile fractions (F2–F3). Gypsum reduced F1 by ∼30% in San Antonio soils with minimal pH change, coincident with increased carbonate- and oxide-bound Pb. Biochar + lime reduced F1 by ∼50% in Baltimore soils, driven by a 0.4–0.8 pH increase and enhanced carbonate- and organic-bound Pb (F2–F4). Alum reduced F1 by ∼28% in Detroit soils, with transient pH shifts and strong increases in oxide-bound Pb (F3).ConclusionDespite contrasting soil chemistries, all treatments achieved rapid and statistically significant Pb stabilization via distinct mechanisms, including Ca2+-facilitated precipitation, pH-driven surface complexation, and Al-hydroxide sorption. This work provides a mechanistic, transferable framework for tailoring low-cost, in situ amendments to local soil geochemistry to durably reduce Pb bioavailability and exposure risk in urban residential soils.